2016
DOI: 10.7869/djo.161
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Sutures - A Review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In the current study, SEM images of the bioabsorbable sutures during different time points of degradation, confirm surface degradation as the primary mechanism of degradation (Figure 11C). This form of degradation is ideal in suture materials where a sudden, rapid loss of suture material can lead to wound dehiscence and failure of the wound to heal 47 . However, gradual removal of the material from the bioabsorbable suture surface will provide continuous, diminishing support to the wound as it heals and regains its own strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, SEM images of the bioabsorbable sutures during different time points of degradation, confirm surface degradation as the primary mechanism of degradation (Figure 11C). This form of degradation is ideal in suture materials where a sudden, rapid loss of suture material can lead to wound dehiscence and failure of the wound to heal 47 . However, gradual removal of the material from the bioabsorbable suture surface will provide continuous, diminishing support to the wound as it heals and regains its own strength.…”
Section: Resultsmentioning
confidence: 99%
“…This form of degradation is ideal in suture materials where a sudden, rapid loss of suture material can lead to wound dehiscence and failure of the wound to heal. 47 However, gradual removal of the material from the bioabsorbable suture surface will provide continuous, diminishing support to the wound as it heals and regains its own strength. In Figure 11C, only a single, thin layer of the bioabsorbable suture remained after 28 days of incubation.…”
Section: In Vitro Drug Release Of the Lipid-drug Coated Bioabsorbable...mentioning
confidence: 99%
“…Nylon (polyamide suture), a synthetic non absorbable suture has two forms of presentation: monofilament and braided. Monofilament nylon has high tensile strength and minimal tissue reactivity [19]. When analyzing the microbial affinity of the two types of nylon threads, researchers found that braided has five to eight times higher affinity when compared to monofilament, this being attributed to the capillary nature of braided materials [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…The material used is determined by the tissue's requirements. An increasing number of materials and suturing techniques are described in the literature [ 3 ]. The sutures used in dentoalveolar surgery represent a risk factor for the healing of surgical wounds because they are prone to the adherence of pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%